Children of the Levee - Hearn, Lafcadio, 1850-1904 (Book collections on Project MUSE., 1957)
Cincinnati in the 1870's was the largest inland city in the nation. Much of its prosperity and growth it owed to the commerce which floated along its Ohio River boundary on the way between Pittsburgh and New Orleans. This traffic also sustained a unique African American culture -- saloonkeepers, boardinghouse operators, entertainers, and women who served the steamboat hands between trips. Into this great western metropolis came young Lafcadio Hearn, who after several tentative starts became a newspaper reporter first for the Enquirer and then for the Commercial. Hearn's twelve sketches -- here reprinted as a unit for the first time -- are perceptive and sympathetic, yet not highly subjective and romanticized. Collectively they form an important comprehensive picture of African American life in a border city just after the Civil War.